Marine Deep Biosphere Microbial Communities Assemble in Near-Surface Sediments in Aarhus Bay - Petro, Caitlin; Zäncker, Birthe; Starnawski, Piotr; Jochum, Lara M.; Ferdelman, Timothy G.; Jørgensen, Bo Barker; Røy, Hans; Kjeldsen, Kasper U.; Schramm, Andreas (Frontiers in Microbiology, 2019)
Analyses of microbial diversity in marine sediments have identified a core set of taxa unique to the marine deep biosphere. Previous studies have suggested that these specialized communities are shaped by processes in the surface seabed, in particular that their assembly is associated with the transition from the bioturbated upper zone to the nonbioturbated zone below. To test this hypothesis, we performed a fine-scale analysis of the distribution and activity of microbial populations within the upper 50 cm of sediment from Aarhus Bay (Denmark). Sequencing and qPCR were combined to determine the depth distributions of bacterial and archaeal taxa (16S rRNA genes) and sulfate-reducing microorganisms (dsrB gene). Mapping of radionuclides throughout the sediment revealed a region of intense bioturbation at 0-6 cm depth. The transition from bioturbated sediment to the subsurface below (7 cm depth) was marked by a shift from dominant surface populations to common deep biosphere taxa (e.g. Chloroflexi & Atribacteria). Changes in community composition occurred in parallel to drops in microbial activity and abundance caused by reduced energy availability below the mixed sediment surface. These results offer direct evidence for the hypothesis that deep subsurface microbial communities present in Aarhus Bay mainly assemble already centimeters below the sediment surface, below the bioturbation zone.